APPROACHES FOR DEVELOPING GENERIC SKILLS IN BUILDING TECHNOLOGY GRADUATES FOR GLOBAL COMPETITIVENESS - Oviawe, Jane Itohan; Uwameiye, R. (Universitas Ahmad Dahlan, 2020)
The need to inculcate generic skills into graduates to meet the demands of the ever dynamic workplace has been of concern to stakeholders in education and the world of work. This concept of a global competitiveness, and generic skills were reviewed and discussed. This paper also examined the importance of generic skills; and factors influencing generic skills development among graduates were highlighted. This factors calls for different approaches and shift in pedagogy in developing generic skills for global competitiveness which include: change in instructional delivery, from the traditional method of instruction to cooperative learning model. It also involves integration and contextualized learning, creating world class spaces for learning, enhanced utilization of technology and inclusive learning and teaching environment for producing global workers in building technology.